Hubungan Nilai Biodiversitas dan Serapan Karbon Vegetasi pada Agroekosistem Sawah Irigasi dan Kebun di Sub DAS Tuntang Hulu, Kabupaten Semarang, Jawa Tengah, Indonesia: Correlation Between Biodiversity and Carbon Sequestration in Vegetation Across Irrigated Rice and Plantation Agroecosystems in the Upper Tuntang Sub-Watershed at Semarang Regency, Central Java - Anugraheni, Eliza; Sutrisno, Alfred Jansen; Savitri, Galuh Windi; Nugrahanto, Bernardinus Arga; Simanjuntak, Bistok Hasiholan (Faculty of Agricultural Technology, University of Jember, 2025)
Irrigated rice fields with flooded cultivation systems tend to produce more carbon than they sequester, as the vegetation is dominated solely by rice plants. In contrast, plantation agroecosystems, which contain a more diverse range of plant species, have greater potential for carbon sequestration due to their higher biomass. This study aimed to analyze the relationship between plant biodiversity and vegetation carbon sequestration in irrigated rice fields and plantation areas within the Upper Tuntang Sub-watershed, at Semarang Regency, Central Java. The research involved 48 sample plots, consisting of 8 irrigated rice field sites and 40 plantation sites, selected based on carbon potential using NDVI data. Research stages included establishing sampling plots, plant species identification, and measuring both biodiversity and vegetation carbon sequestration. Results showed that the biodiversity index in irrigated rice fields fell into the low category, as rice was the only dominant species. In contrast, the plantation exhibited medium biodiversity indices due to the presence of more varied plant species. Carbon sequestration was highest (7,68) at point 5 and lowest (0,01) at point 7 in irrigated rice fields, while in plantation it was highest (230,00) at point 37 and lowest (0,01) at point 39. To assess the relationship between biodiversity and carbon sequestration, the plots were classified into three vegetation structure types: (1) understory plants, (2) understory plants and trees, and (3) understory plants, trees, and shrubs. A significant relationship between biodiversity and carbon sequestration was observed in plots containing both understory plants and trees with sig. value (2-tailed) of 0,047. However, no significant relationship was found in plots dominated solely by understory vegetation with sig. value (2-tailed) of 0,897, nor in plots containing understory, trees, and shrubs with sig. value (2-tailed) of 0,255. The research can serve as a basis for sustainable agroecosystem management, as it shows that increasing plant biodiversity can contribute significantly to increased vegetation carbon sequestration in the Upper Tuntang Sub-Watershed. Keywords: biodiversity, carbon sequenstration, plantation, rice field